Towards Equity: Projecting and Converging the Human Development Index in Indonesia - Nayaka Artha Wicesa,; Axellina Muara Setyanti; Silvi Asna Prestianawati (Universitas Udayana, 2024)
Human development has become an imperative for Indonesia amid the ongoingdemographic bonus. However, various challenges persist in the realm of humandevelopment in the country, as evidenced by disparities in Human Development Index(HDI) achievements. This research aims to project Indonesia's HDI for the years 2023, 2024,2035, and the